Predictors of hearing technology use in children. - Booysen, Surida; le Roux, Talita; Masenge, Andries; Swanepoel, De Wet (International Journal of Audiology, 2022)
To identify and describe predictors of daily hearing technology (HT) use in children. Retrospective review of clinical records. Multiple regression analyses were performed to identify predictors. The sample included 505 children (<11 years of age) using hearing aids (HAs), cochlear implants (CIs), and bone conduction hearing devices (BCHDs). Average HT use was 9.4 h a day. Bivariate analyses yielded 31 potential predictors from the 42 variables included. The general linear model (p < 0.01, R2 = 0.605) identified 10 interacting factors that significantly associated with increased HT use. Intrinsic predictors of increased HT use included older chronological age, more severe degrees of hearing loss and older ages at diagnosis and initial HA fitting. Extrinsic predictors included the child's ability to independently use HT, at least one CI as part of the HT fitting, coordinated onsite audiological management, self-procured batteries, auditory-oral communication mode and regular caregiver intervention attendance. Average HT use was high, approximating hearing hours of peers with normal hearing. CI recipients demonstrated higher HT use compared to children using other HT. The newly identified factors can predict and increase HT use in children while contributing to evidence-based intervention services that promote optimal auditory-based outcomes.